Psychological Distress in Adults With Congenital Heart Disease Over the COVID‐19 Pandemic - Mikyla L. Janzen; Karen LeComte; Gnalini Sathananthan; Jia Wang; Marla Kiess; Santabhanu Chakrabarti; Jasmine Grewal (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background This study sought to better understand the experiences of adults with congenital heart disease throughout the pandemic. Objectives were to determine (1) psychological distress before and throughout the pandemic; (2) changes in day‐to‐day functioning; and (3) the percentage of adults with congenital heart disease who experienced COVID‐19 related symptoms, underwent testing, and tested positive. Methods and Results This was a cross‐sectional study paired with retrospective chart review. A web‐based survey was distributed to patients between December 2020 and January 2021. Patients reported on psychological distress across 5 categories (Screening Tool for Psychological Distress; depression, anxiety, stress, anger, and lack of social support), whether they experienced symptoms of COVID‐19 and/or sought testing, and changes to their work and social behavior. Five hundred seventy‐nine survey responses were received, of which 555 were linked to clinical data. Patients were aged 45±15 years. The proportion of patients reporting above‐threshold values for all Screening Tool for Psychological Distress items significantly increased during the early pandemic compared with before the pandemic. Stress returned to baseline in December 2020/January 2021, whereas all others remained elevated. Psychological distress decreased with age, and women reported persistently elevated stress and anxiety compared with men during the pandemic. A consistent trend was not observed with regard to American College of Cardiology/American Heart Association anatomic and physiologic classification. Fifty (9%) patients lost employment because of a COVID‐19–related reason. COVID‐19 symptoms were reported by 145 (25%) patients, 182 (31%) sought testing, and 10 (2%) tested positive. Conclusions A substantial proportion of adults with congenital heart disease reported clinically significant psychological distress during the pandemic.